Accuracy of spot color reproduction in a 7-color, expanded gamut, flexographic printing system - El Asaleh, Reem; Habekost, Martin; Sharma, Abhay (Journal of Print and Media Technology Research, 2022)
Expanded gamut printing involves expanding the number of process colors (cyan, magenta, yellow and black) by orange, green and violet colors to reproduce many spot colors with the new fixed ink set (CMYKOGV). This study focuses on evaluating flexographic expanded gamut printing on a narrow web flexographic label press located at Toronto Metropolitan University. Esko Equinox and GMG OpenColor expanded gamut software solutions were used, where each system was tested with its own proprietary characterization test chart. The Idealliance Expanded Color Gamut (ECG) test target was also used in this study. A verification test chart was created, with selected Pantone spot colors. The test chart was then processed using the characterization data from the proprietary and nonproprietary characterization press runs. The builds of the selected Pantone colors were analyzed and CIEDE2000 color difference was calculated. Both software solutions did better in regards to color accuracy with their proprietary characterization targets than using the data gathered from the Idealliance ECG small chart.